Significance of and Comparative Trends in Procedural Regulation of Right to Information - Polonca Kovač (Central European Public Administration Review)
Any legal right is (more) efficiently pursued if sufficient procedural regulation supports its substantive setting. This article is dedicated to an analysis of procedural regulation of right to information (RTI) since its significance is increasing in terms of developing good governance and good administration within contemporary transparent, open and collaborative society. The comparative analysis of selected countries (USA, Ireland, Sweden, Austria, Germany, Slovenia, Croatia) included herein proves that selected procedural institutions, such as time limits and an appeal to an independent body or judicial review, contribute to a significantly higher level of implementation of the RTI in practice as also indicated by several international studies. In conclusion, the author recommends certain good practices, especially significance of RTI implementation in relation to different authorities in the context of administrative procedure guaranteeing constitutional and supranational transparency principles.